Messaging on Wasap and university millennials in Cotopaxi, challenges for higher education in Ecuador - Gómez-Castells, Máximo Ricardo (2021)
In order to make an approach to the messaging that the student body reveals in Wasap from the perspective of the interpreter and to establish the challenges that this represents for Higher Education in Ecuador, the investigation is carried out, such purpose constitutes the contribution to a revelation of the effects produced in the receptive discourse whose reading passes through sociolinguistics, language philosophy and pragmatics, the convergence of such arguments in the pedagogical field is a possibility for teaching from digital discourse. This article offers an exploration of the potential relationship between the use of instant messaging and the formation of interpreters based on the establishment of theoretical and methodological assumptions of sociolinguistics in university millennials of the National and Foreign Languages ​​Pedagogy Career from the Technical University of Cotopaxi in Ecuador. The research was of an exploratory type and a qualitative methodology in which a strategy of complementarity of the methods and techniques of document analysis, group and individual interview, survey and the hermeneutical analysis of discourse was implemented. The sample was selected through non-probability sampling, being made up of 10 students. The results revealed the series of interpreters that Ecuadorian university millennials generate and the linguistic variations that typify their discourse; information from where the rules present in the reception were extracted, as well as a taxonomy of the interpreters present in the digital platform studied constituting a model of discourse as a synthesis of the instant messaging used by the students. Messaging where interpreters are configured that reveal their significant creativity, from which considerations were derived about the need to generate teaching procedures based on Peirce's trilogy where the student body forms cognitive capacities on the transcendence of the linguistic imaginary in the enrichment of the language.